Synthesis, physical-chemical and biological properties of 8-aminoderivatives of 7-(2-hydroxy-2-phenylethyl)theophylline - D. G. Ivanchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
The search for new high-performance antimicrobial compounds remains one of the most important tasks of modern pharmaceutical chemistry, despite the wide range of modern natural, synthetic and semi-synthetic drugs for the treatment of infectious diseases. This is especially true for the naturally occurring compounds, new non-toxic and effective drugs can be created by their chemical modification for the treatment of various infectious pathologies. Recent researches in this area pay significant interest to new synthetic derivatives of xanthine.